Medicaid data. - United States. Medicaid Bureau. Division of Analysis and Evaluation ([Washington] Dept. of Health, Education, and Welfare, Health Care Financing Administration, Medicaid Bureau, Division of Analysis and Evaluation., 1977)
"Medical assistance (Medicaid) financed under Title XIX of the Social security act."
"Medical assistance (Medicaid) financed under Title XIX of the Social security act."
Keywords: Medicaid -- Statistics -- Periodicals; Medicaid -- Statistics